Continuous Logit Polycentric City Model - Matthias Wrede (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
This paper analyzes a closed linear polycentric city with homogenous households who probabilistically select their workplace and residence locations. The study utilizes a continuous logit model to describe household location choices. In contrast to the classic urban model with deterministic location choices, the continuous logit model predicts noticeable direct effects of more than one workplace on land rents, asymmetry of the land rent schedule around secondary business districts, incomplete segregation of citizens who work in different business centers and, therefore, cross commuting, and incomplete segregation of workers and farmers.
Keywords: R13; R14; R12; 330